Molecular Investigations of Ankyrin Specific to HIV-1 Capsid in Inhibition of Viral Replication and Direct Cell-to-Cell Viral Transfer - Sutpirat Moonmuang (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
A designed ankyrin repeat scaffold protein (AnkGAG1D4), which recognizes the human immunodeficiency virus-1 (HIV-1) capsid (CA) protein, was formerly established and described as an HIV-1 inhibitor that interfere the assembly process of HIV-1 replication cycle resulting in the significant reduction of viral progeny. However, the details of mode and molecular mechanisms of action of AnkGAG1D4 during the late stages of the HIV-1 replication cycle have not been investigated. Using stimulated emission-depletion microscopy, we demonstrated that Gag distribution was clearly interrupted at the inner cell membrane leaflets of HIV-1 transfected cells. This implied that Gag polymerization was disturbed by AnkGAG1D4. Disturbing of Gag polymerization resulted in the reduction of viral release without effecting proteolytic processing of Gag as determined by measuring the HIV-1 protease activity, induction of Gag accumulation inside HIV-1 producer cells, and reduction of the CD81 tetraspanin organization at the plasma membrane of HIV-1 transfected cell. Moreover, reverse transcription-quantitative polymerase chain reaction experiments were performed to determine levels of viral and cellular RNAs, and the packaging efficiency of RNAs. Our results revealed that AnkGAG1D4 impeded the Gag precursor protein from packaging of viral and cellular RNAs for encapsidation into viral particles. Finally, the intercellular transmission of HIV-1 through direct cell-to-cell contact was established. The cell-to-cell transmission of HIV-1 from Sup-T1 to THP-1 was considerably prohibited by myristoylated AnkGAG1D4. These findings convey additional information on the antiviral activity of AnkGAG1D4 at late stages of the HIV-1 replication cycle which will be valuable for either protein scaffold or chemical drug design to prevent the HIV assembly at inner membrane.